The People's Health - Hastings, Somerville, 1878-1967 (London : The Labour Party)
1932-07 1932 1930s 24 pages medicine and surgery are readily obtainable and where any necessary pathological examinations can be carried out. All the hospitals will be closely linked together to form a single hospital system so that cases of special difficulty can be readily transferred from one to another as required, and for this and many other purposes an efficient ambulance service is essential. Each county will have its own general hospital or hospitals in the county town and other large centres. The hospitals will be staffed by specialists who will also see cases in the Health Centres. The hospitals will receive patients sent them direct by the Home doctors of the county (who will be encouraged to keep in touch with their patients while in hospital) and in addition cases transferred from the smaller hospitals of the county. The needs of medical education will probably be best met by attaching medical schools to the county hospitals in university and certain other towns. Most of the patients in these hospitals will be drawn from the county in which the hospital is situated and the cost of their treatment will be met by the county. But, in addition, it will be possible to transfer to these hospitals cases of special difficulty or interest from any part of the country. The cost of treatment of such patients would be paid for by the county from which they came. In addition to these county and university hospitals, there will be smaller hospitals, especially for accidents and for chronic or less serious cases, dotted about the county. In charge of each of these hospitals will be a capable resident medical officer Where members of the Home service are living sufficiently near, they will be encouraged to continue the treatment of their patients after their admission to these hospitals. In addition, specialists attached to the county or university hospitals, will be called upon to see patients in consultation in the wards of these hospitals, either when they attend the adjacent Health Centre or when specially sent for. The close association between these local hospitals and the county hospital will make easy the transfer of cases to the latter when required. There will also be needed one or more large hospitals for infectious disease in each county. It is a great mistake to provide one of these hospitals in every urban district, as treatment is better carried out by doctors with special experience. The centralisation of hospital treatment both for infectious and general diseases which has been recommended, will undoubtedly result in some hardship to the friends of patients who had been removed to hospitals some distance from their homes. The resulting advantages from increased facilities for treatment will, however, more than compensate for this. The Sanatorias for Tuberculosis, both pulmonary and surgical, will also be administered by this Sub-committee. 11 292C/155/1/1